Water Quality Index Using Modified Random Forest Technique: Assessing Novel Input Features - Wen Yee Wong; Ayman Khallel Ibrahim Al-Ani; Khairunnisa Hasikin; Anis Salwa Mohd Khairuddin; Sarah Abdul Razak; Hanee Farzana Hizaddin; Mohd Istajib Mokhtar; Muhammad Mokhzaini Azizan (TECH SCIENCE PRESS, 2024)
Indexed by WOS/SCOPUS/ERA